Assessment of Thermal Comfort and Building-Related Symptoms in Air-Conditioned Offices in Tropical Regions: A Case Study in Singapore and Thailand - Sikram, Tanadej; Ichinose, Masayuki; Sasaki, Rumiko (Frontiers in Built Environment, 2020)
Indoor thermal environment is important for maintaining comfort and health. In a tropical region, it becomes more critical when the air-conditioning system consumes excessive energy for a whole year. This study aims to clarify the impact of thermal environment on human comfort and building-related symptoms in air-conditioned offices. A field study was conducted in office spaces in Singapore and Thailand from 2017 to 2019 by installing data loggers to measure thermal variables together with a questionnaire survey. As a result, the psychometric charts of ASHRAE 55 show that most of the measured thermal environments were fitted to the 1.0 clo comfort zone, which was not recommended for people in this region. Overcooling determined the cause of high discomfort when people felt cold and preferred a warmer temperature. Based on Griffith’s method, average comfort temperatures were 24.8 °C (Singapore) and 24.0 °C (Thailand). The probit analysis illustrated that the comfort temperature range for a dissatisfaction of 20% was 23.6–26.4 °C (Singapore) and 22.9–25.6 °C (Thailand). These comfort temperature ranges which were higher than the measured values reflected the clothing adaptation and the personal complaints. Symptoms were reported in the coldest temperature group (21–22 °C), with the highest odds ratio of symptom occurrence. The thermal sensation vote defined that the higher rate of symptoms belonged to the colder-than-neutral side, whereas the thermal comfort vote could not well predict the symptom occurrence. The intention of enhancing comfort and promoting better health conditions in the offices of these regions was discussed, while considering warmer indoor temperatures.